2007
DOI: 10.1073/pnas.0709205105
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic B cell depletion impairs adaptive and autoreactive CD4+T cell activation in mice

Abstract: CD20 antibody depletion of B lymphocytes effectively ameliorates multiple T cell-mediated autoimmune diseases through mechanisms that remain unclear. To address this, a mouse CD20 antibody that depletes >95% of mature B cells in mice with otherwise intact immune systems was used to assess the role of B cells in CD4 ؉ and CD8 ؉ T cell activation and expansion in vivo. B cell depletion had no direct effect on T cell subsets or the activation status of CD4 ؉ and CD8 ؉ T cells in naive mice. However, B cell deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
256
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(271 citation statements)
references
References 48 publications
(45 reference statements)
12
256
1
2
Order By: Relevance
“…That B cell trafficking preceded T cell trafficking during repair suggests that B cells could be involved in regulating T cell infiltration and expansion in postischemic kidney. An important role of B cells as antigen-presenting or co-stimulatory cells was also reported in animal models of autoimmune disease 30 ; however, adoptive B cell transfer into MT mice did not affect T cell trafficking into the postischemic kidneys, suggesting that B cells could be acting on tubular repair independent of T cell trafficking.…”
Section: Discussionmentioning
confidence: 73%
“…That B cell trafficking preceded T cell trafficking during repair suggests that B cells could be involved in regulating T cell infiltration and expansion in postischemic kidney. An important role of B cells as antigen-presenting or co-stimulatory cells was also reported in animal models of autoimmune disease 30 ; however, adoptive B cell transfer into MT mice did not affect T cell trafficking into the postischemic kidneys, suggesting that B cells could be acting on tubular repair independent of T cell trafficking.…”
Section: Discussionmentioning
confidence: 73%
“…CD20 C B cells contribute both to humoral immunity as antibody-producing cells, but also to cellular immunity by serving as antigen-presenting cells (APCs) and/or by providing costimulatory signals to T cells. 19,20 A favorable effect of tumor-infiltrating B cells on patient prognosis was previously reported in cutaneous melanoma, 21 breast cancer 22 and ovarian cancer, 23 but the mechanism linking the accumulation of these cells in the tumor microenvironment and better prognosis remains poorly understood. Nielsen et al found that tumor-infiltrating B cells expressed markers of antigen presentation and could have a function of professional APCs to support the T cell-mediated immune anticancer response.…”
Section: Discussionmentioning
confidence: 99%
“…However, B cells can influence T cell function through a variety of means (21,(34)(35)(36)(37)(38). It has been suggested that they are involved in regulating the activation status and number of effector T lymphocytes based on observations of abnormal CD4 ϩ T cell responses in B cell-deficient mice (36, 37).…”
Section: Discussionmentioning
confidence: 99%